Absorption by the rat of alginate labelled with carbon-14. - Humphreys, E; Triffitt, J (1968)
SODIUM alginate is usually present in trace amounts in prepared foodstuffs but, because of its effectiveness in inhibiting strontium absorption, the addition of larger amounts to the diet has been proposed as a means of protecting a population exposed to dangerously high levels of strontium-90 in the food1-7. The fate of ingested alginate, however, has been the subject of relatively few investigations; one report8 concluded that gastrointestinal absorption of alginate varies from 3-88 per cent. Experiments are described here, showing that there is no significant absorption of alginate by rats from a diet in which the alginate is present in the proportion used to inhibit strontium absorption. © 1968 Nature Publishing Group.